Regional Financial Monitoring Models With Community Participation And Public Policy Transparency As Moderators - Yohannis Tamaela, Eduard; Pattiasina, Victor; B. Dasinapa, Margaretha; Marani, Yohanes; Ari Duri, Jimmi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to examine the effect of legislative members’ knowledge of the budget on the regional development budget with public participation and transparency of public policy as a moderating variable. The sample of the current study were members of the legislative body of the Regional People’s Representative of Papua Province in the period 2019-2024. The number of respondents in this study was 45 legislative members. Hypothesis testing was examined using simple linear regression analysis and MRA (moderated regression analysis). The results showed that the knowledge of legislative members about the budget has had a positive and significant effect on regional financial supervision, which proved that the higher the legislative member’s knowledge about the budget, the better the supervision of regional finance. Other results show that public participation and transparency of public policies are proven to be able to positively and significantly influence the relationship of the knowledge of legislative members about the budget towards the Regional Development Budget. This finding indicates that public participation and transparency in public policy have proven to strengthen the knowledge of legislators about the budget in increasing the Regional Development Budget.